Development Of an Attendance System Using Rfid Based On The Internet of Think - Sujono Sujono; Tri Siswoyo; Zulfikar Zulfikar (NEWTON: Networking and Information Technology, 2026)
The attendance system is an important component in the world of education to monitor student attendance regularly and accurately. However, manual attendance methods that are still widely used, such as recording in books, have various disadvantages such as prone to recording errors, data manipulation (absenteeism), and making the attendance recapitulation process difficult. This research aims to develop an automatic attendance system using Radio Frequency Identification (RFID) technology integrated with the Internet of Things ( IoT ). This system is designed so that the attendance recording process can be carried out automatically, in real-time, and directly stored in a web-based database. The system development method uses a prototyping approach, with stages of communication, quick planning, quick design, construction, and feedback from users. The hardware used includes ESP32, MFRC-522 RFID module, 16x2 LCD, buzzer, and push button. While the software is built using PHP Native, MySQL, and Arduino IDE. The system has three main modes, namely Data Add Mode, Opt-In Mode, and Opt-Out Mode. Attendance data will be sent directly to the server and can be accessed by teachers or officers through the web dashboard. The test results using the black box method show that the system is running according to the expected function. The implementation of this system has been proven to improve the efficiency and accuracy of recording student attendance, as well as reduce the administrative burden on the school. The system also has the potential to be further developed with notification features or integration into other academic